BACTERIAL CONTAMINATION TEST IN POWDER-FORMULATED Helicoverpa armige-ra NUCLEAR POLYHEDROSIS VIRUS (HaNPV1) SUBCULTURE - Mia Miranti; Hikmat Kasmara; Nurullia Fitriani; Melanie Melanie; Inas Qurrata A'yun; Yolani Syaputri; Febri Doni; Madihah Madihah; Sri Rejeki Rahayuningsih; Nabilah Sekar Azizah; Wawan Hermawan (Jurnal Bioteknologi dan Biosains Indonesia, 2023)
The Helicoverpa armigera Nuclear Polyhedrosis Virus (HaNPV1) is a subculture derived from the original HaNPV, and it has been cultivated in Spodoptera litura larvae as an alternative host. HaNPV1 was subsequently formulated using gypsum and talcum as carrier media. Following this formulation, a bacterial contamination test was conducted to assess the quality of the viral formulation.  The experiment was arranged in the randomized factorial block design (RFBD) with 2 replications. The viral formulations was stored for 16 weeks and the samples were taken every two weeks for contamination analysis. The data was then analyzed with the analysis of variance (ANOVA) and a post-hoc using Duncan’s Multiple Range test. The variable observed was the number of the bacterial colonies cultivated on the specific media i.e., Nutrient Agar (NA), Salmonella Shigella Agar (SSA) and Eosin Methilen Blue Agar (EMB). The results showed that the bacterial contaminants was detected from 0 to 12 weeks of storage time. However, the highest contamination was found in viral formulation after 8 weeks of storage time and the highest bacterial contaminations were recorded from all viral formulation tested in NA. The results indicated that the bacterial contamination were found around 1.45 × 109 cfu/gram and 1.97 × 109 cfu/gram in gypsum and talcum formulations, respectively. On SSA and EMB media, the bacteria contaminants from all formulation found in 8 weeks of storage time, but Salmonella, Shigella, or Escherichia coli (aspathogenic bacteria) were not found. After 12 weeks storage time, there was no indication of  contamination found in all media. Furthermore, Bacillus species was found as a most dominant contaminant in all samples. In conclusion, although the viral formulations using gypsum and talc were not contaminated by pathogenic bacteria such Salmonella, Shigella, or E. coli. Nevetherless, the viral formulation was still easily contaminated by other non-pathogenic bacterial species. Thus, a more standardized and stricted strategy needs to be developed for a better viral formulation product.